Rancangan Sistem Informasi Penggajian Pada Perusahaan Jasa Bengkel - Permatasari, Angelina; Cristian, Lianawati (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The aim of the research is to analyze existing problems on companies in the automotive service industry, namely, analyzing the current payroll system, identifying needs, and modify and design a better payroll system accordingly. Methods used are analysis methods and design methods. Analysis methods conducted are literature study, field observation, survey on current system, needs analysis survey, identifying information needs, interview, and design methods used is Object Oriented Analysis and Design (OOAD). Obtained results are improved payroll system which has been done manually before. It can be concluded that a computerized payroll information system can solve existing problems and old procedures.